The effectiveness of lavender and jasmine aroma therapy towards pain levels - Indah Wijayanti; Sri Handayani; Menik Sri Daryanti; Claudia Banowati Subarto; Farida Aryani (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: The maternal mortality rate in Southeast Asian countries is Indonesia 190 per 100,000 live births, Vietnam 49 per 100,000 live births, Thailand26 per 100,000 live births, Brunei 27 per 100,000 live births, and Malaysia 29 per 100,000 live births (WHO, 2015). Data on maternal mortality in the Special Region of Yogyakarta in 2020 found 40 cases, an increase from the previous year, which was 36 cases. In the Bantul district there are 20 cases of maternal mortality(DIY Health Office, 2020). Labor pain relief methods are divided into non-pharmacological (psychoprophylactic, hypnosis, acupuncture, touch healing therapy, relaxation exercises, massage therapy, music therapy) and pharmacological (systemic drugs, inhalation anesthetics, general anesthesia, regional anesthesia) (Tanvisut et al., 2018).Objectives:This study aims to determine the effect of lavender and jasmine aromatherapy on pain levels in the first stage of labor at the Bina Sehat Clinic.Methods: Quasi experimentwith pretest and posttest group design. a sample of 38 respondents using the formula (Lemeshow et al., 1997) in Sastroasmoro and Ismail (2011). Sampling technique with simple random samplingResults:Shows that jasmine aromatherapy is more effective in reducing pain levels in first-stage mothers than lavender aromatherapy at the Bina Sehat Clinic. There is a significant effect of the level of labor pain in the first stage before and after the lavender and jasmine aromatherapy intervention period.Conclusions:Jasmine aromatherapy was more effective in reducing pain levels in first-stage labor than lavender aromatherapy at the Bina Sehat Clinic with a Z_Wilcoxon value obtained at -4.001 and a significant value of 0.000 (p<0.000). There was a significant effect on the results of the first stage of labor pain before and after the lavender and jasmine aromatherapy intervention period, which was -4.143 and a significant value of 0.000 (p<0.000).